Aspectos epidemiológicos e doenças associadas à infecção retroviral em gatos submetidos à necropsia - Lorenzetti, Douglas Miotto (2021)
Among the retroviruses of veterinary interest are the feline leukemia virus (FeLV) and the feline immunodeficiency virus (FIV), the most important domestic cat pathogens in the world. FeLV is mainly related to the occurrence of hematopoietic neoplasms. FIV, on the other hand, usually contributes to the development of opportunistic diseases, due to immunosuppression. Although there are several studies relating these infections to a variety of epidemiological and clinical aspects, there is little information about the diseases that lead to the death of infected cats. The aim of this study was to determine the occurrence of infections by FIV and FeLV in cats from the central region of Rio Grande do Sul (RS) that underwent necropsy, as well as to evaluate the relationship of infectious status with the epidemiological characteristics and the definitive diagnoses. For that, between the years 2014 and 2020, epidemiological data and definitive diagnoses of 350 cats submitted to necropsy were registered in an anatomopathology service in the central region of RS. During the necropsy of these cats, blood samples were collected for the diagnosis of FIV and FeLV through the SNAP FIV/FeLV Combo test (IDEXX Laboratories). Among the animals submitted to necropsy, 216/350 (61.7%) were males and 134/350 (38.3%) females, with an average age of 5 years (1 month to 24 years). The prevalence for infection with FIV, FeLV or both retroviruses concomitantly was 9.1%, 29.4% and 5.4%, respectively. The average age of death for cats infected with for infection by FIV, FeLV or both retroviruses concurrently was 6 years (3 to 15 years), 3 years (4 months to 12 years) and 4 years (8 months to 7 years) respectively. The main diseases identified in FeLV positive cats were lymphomas (29/48; 60.4%), leukemias (23/23; 100%) and feline infectious peritonitis (12/19; 47.4%), mainly the dry form (11/14; 78.6%). Among the positive FIV cats, the main disease diagnosed was Feline Acquired Immunodeficiency Syndrome (FAIDS) (11/11; 100%), followed by the diagnosis of pneumonia (8/17; 47%). Among the animals negative for FeLV and FIV, chronic kidney disease was the main diagnosis (17/19; 89.5%). Although both retroviral infections affected more male cats, there was no statistical difference. FeLV infection is associated with younger cats, between six months and six years of age, while FIV infection affects older cats, between three and ten years of age. Thus, compared to uninfected cats, it is possible to state that FeLV infection significantly reduces feline life expectancy, mainly because it is related to neoplastic disorders. Also, FIV infection is related to infectious and parasitic diseases, increasing the frequency of this group of diseases in the local feline population.